Objectively measured physical activity and fat mass in children: a bias-adjusted meta-analysis of prospective studies. - Desiree C Wilks; Stephen J Sharp; Ulf Ekelund; Simon G Thompson; Adrian P Mander; Rebecca M Turner; Susan A Jebb; Anna Karin Lindroos (PLoS ONE)
Background Studies investigating the prevention of weight gain differ considerably in design and quality, which impedes pooling them in conventional meta-analyses, the basis for evidence-based policy making. This study is aimed at quantifying the prospective association between measured physical activity and fat mass in children, using a meta-analysis method that allows inclusion of heterogeneous studies by adjusting for differences through eliciting and incorporating expert opinion. Methods Studies on prevention of weight gain using objectively measured exposure and outcome were eligible; they were adopted from a recently published systematic review. Differences in study quality and design were considered as internal and external biases and captured in checklists. Study results were converted to correlation coefficients and biases were considered either additive or proportional on this scale. The extent and uncertainty of biases in each study were elicited in a formal process by six quantitatively-trained assessors and five subject-matter specialists. Biases for each study were combined across assessors using median pooling. Results were combined across studies by random-effects meta-analysis. Results The combined correlation of the unadjusted results from the six studies was -0.04 (95%CI: -0.22, 0.14) with considerable heterogeneity (I² = 78%), which makes it difficult to interpret the result. After bias-adjustment the pooled correlation was -0.01 (95%CI: -0.18, 0.16) with apparent study compatibility (I² = 0%). Conclusion By using this method the prospective association between physical activity and fat mass could be quantitatively synthesized; the result suggests no association. Objectively measured physical activity may not be the key determinant of unhealthy weight gain in children.